Catalyst‐Controlled 1, 2‐ and 1, 1‐Arylboration of α‐Alkyl Alkenyl Arenes. Issue 6 (9th January 2019) - Bergmann, Allison M.; Dorn, Stanna K.; Smith, Kevin B.; Logan, Kaitlyn M.; Brown, M. Kevin
Abstract: Two methods are reported for the 1, 2‐ and 1, 1‐arylboration of α‐methyl vinyl arenes. In the case of 1, 2‐arylboration, the formation of a quaternary center occurred through a rare cross‐coupling reaction of a tertiary organometallic complex. 1, 1‐Arylboration was enabled by catalyst optimization and occurred through a β‐hydride elimination/reinsertion cascade. Enantioselective variants of both processes are presented as well as mechanistic investigations. Abstract : Keep your options open : Methods were developed for both the 1, 2‐ and 1, 1‐arylboration of α‐alkyl alkenyl arenes, including enantioselective variants. The formation of quaternary centers by 1, 2‐arylboration occurred through a rare cross‐coupling of a tertiary organometallic complex (see scheme). 1, 1‐Arylboration was enabled by catalyst optimization and occurred through a β‐hydride elimination/reinsertion cascade.